Sengketa Pajak dalam Perspektif Pemeriksa Pajak (Sebuah Studi Fenomenologi) - Tendi Wahyudi; Unti Ludigdo; Ali Djamhuri (Jur. Akuntansi, Politeknik Negeri Malang, 2017)
AbstractThis study aims to reveal and explore new meanings of the tax dispute from the perspective of those directly involved, namely Tax Auditor. Phenomenology is used as a research method to explore these meanings. The research revealed that the essence of tax dispute from the Tax Auditor perspective is “unfinished negotiation”. “Negotiations” are manifested itself in various forms of effort to obtain a “deal”. Not only visible in the form of dissent that are